Comfirmatory Factor Analysis Terhadap Nilai Perusahaan Start Up Di Dunia - Faniza Sari; Dinda Tiara Arini Hutasuhut; Ferry Ferry; Yeni Ariesa; Juli Meliza (Journal of Economic, Bussines and Accounting (COSTING), 2023)
For start up companies that are relatively new and require large funds for development.there are also aspects that affect companies so that they can be valued well or vice versa in international markets.thisstudy aims to examine the effect of capital,equity on firm value moderated by innovation in start up companies in the word for the 2017-2021 period.A quantitative research approach.this type of research is asymentary relations.the sample is 17 companies and 85data.smartpls data analysis.the result of the study are that capital and equity have no company value in start up companies in the world for the 2017-2021 period.capital and equity affect innovation in the world for the 2017-2021 period.innovation has no effect on company value in start up companies in the world for the 2017-2021 period. Keywords: Capital,Equity,Innovation, Company Value